2009
DOI: 10.1111/j.1365-2125.2008.03328.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of intravenous pantoprazole in paediatric intensive care patients

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• The use of intravenous pantoprazole, a proton pump inhibitor, has been increasing in the paediatric intensive care unit.• Despite this increased use, data on the disposition of intravenous pantoprazole in paediatric intensive care patients are very scarce. WHAT THIS STUDY ADDS• Our population approach has determined the pharmacokinetic parameters of intravenous pantoprazole in paediatric intensive care patients and the relative importance of factors influencing its dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
4
13
0
Order By: Relevance
“…The typical population pharmacokinetic parameters from the final model were similar to recent articles investigating the pharmacokinetics of pantoprazole in pediatrics 10 , 31 . The typical CL fell between the reported mean values (1.4 L per hour and 3.0 L per hour), while the volume of distribution at steady‐state (V2 + V3) was lower than the reported mean values (2.2 L and 2.5 L) for these 2 studies.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The typical population pharmacokinetic parameters from the final model were similar to recent articles investigating the pharmacokinetics of pantoprazole in pediatrics 10 , 31 . The typical CL fell between the reported mean values (1.4 L per hour and 3.0 L per hour), while the volume of distribution at steady‐state (V2 + V3) was lower than the reported mean values (2.2 L and 2.5 L) for these 2 studies.…”
Section: Discussionsupporting
confidence: 73%
“…There is limited information regarding the pharmacokinetics of pantoprazole in children. Recently published studies were either limited to single doses of intravenous (IV) or oral pantoprazole, or investigated only IV pantoprazole in a small number (n = 20) of pediatric patients 9 , 10 . The pharmacokinetic characteristics of pantoprazole (linear, short half‐life, lack of drug interactions) make it an attractive agent for pediatric use 11 13 .…”
mentioning
confidence: 99%
“…The dosage of each PPI varies per weight and age as they are rapidly absorbed and metabolized: esomeprazole (0.2-1 mg/kg/day, 1-17 years), omeprazole (0.7-3.5 mg/kg/day, 2-16 years), lansoprazole (0.7-1.44 mg/kg/day, 1-17 years), pantoprazole (0.6-1.2 mg/kg/day) [33-36]. PPI does not develop tachyphylaxis [36]. All kinds of PPIs have similar anti-secretory effects.…”
Section: Managementmentioning
confidence: 99%
“…Those authors found that the clearance of pantoprazole increased with increasing weight and age, and fell with the presence of SIRS, CYP2C19 inhibitors, and liver dysfunction. However, in patients between 6 months and 5 years of age without these factors, pantoprazole clearance was higher than in adults [44].…”
Section: Pharmacokinetics Of Omeprazol In Critically Ill Paediatric Pmentioning
confidence: 74%